The smell of terroir! Olfactory discrimination between wines of different grape variety and different terroir. (June 2017) - Foroni, Francesco; Vignando, Miriam; Aiello, Marilena; Parma, Valentina; Paoletti, Maurizio Guido; Squartini, Andrea; Rumiati, Raffaella I.
Highlights: We tested whether panelists detect olfactory differences of wines. A computer-controlled olfactometer was used to precisely deliver wine odors. Discrimination reflected whether two wines differed by terroir, grape variety, or both. Panelists discriminate wines differing on variety and terroir but not on variety only. Panelists ' smell ' terroir as they discriminate two wines differing only in terroir . Abstract: The French term ' terroir ' refers to the relationship between a particular wine and the specific place where it is produced. To date, no investigation has directly tested in an experimentally-controlled setting whether participants can detect different terroir s in wines, and if their level of expertise can modulate such performance. We investigated wine olfactory discrimination ability by using a computer-controlled olfactometer. Participants' ability to discriminate two wines only based on the olfactory features of their terroir (zone and vineyard), their variety (e.g., cabernet vs. merlot) or both was tested. Olfactory discrimination performance of both novices and wine-professionals reflected whether two wines differed by terroir, variety or both. Performance peaked when wines differed in both terroir and variety, with terroir being more easily discriminated than variety. These results, obtained by controlling for the first time the precision of the olfactory stimulation, provide insightful clues in understanding the wine appreciation process, specifically with respect to the perceptual aspects of terroir .